Temperature and Humidity Control System for Pole-Mounted Metering Circuit Breaker with Artificial Neural Network Methods - Ahmad, Mirza Ghulam; Efendi, Moh. Zaenal; Eviningsih, Rachma Prilian (Faculty of Engineering, Universitas Tanjungpura, 2023)
Pole-mounted Metering Circuit Breaker (PMCB) is a medium voltage protection device. Problems in the PMCB because operating at medium voltage causes insulation problems. The isolation problem that arises is due to partial discharge. Partial discharge can trigger the risk of flashover. In addition, corona discharge causes corrosion of the conductor, the effect is a failure and disconnection of electricity. This control system aims to maintain the temperature and humidity of the PMCB at the nominal values according to the standard. Based on SPLN D3.021-1:2020, it is known that under normal service conditions, the ambient air temperature does not exceed 40 °C and the average temperature for 24 hours does not exceed 35 °C and the highest relative humidity is 100% RH. The control system uses an AC voltage controller which is used to control the input voltage of the heater and exhaust fan so that the temperature and humidity can reach nominal operating conditions. The control method used is an artificial neural network (ANN) to find the ignition angle of the AC voltage controller as a TRIAC control. The test results using the ANN control method, system simulation produces a temperature error of 1.029% and humidity error of 2.48% and the hardware system produces a temperature error of 2.364% and humidity error of 8.673% compared to the set point temperature of 35 °C and humidity of 50% RH. It can be concluded that the ANN control method can maintain the PMCB temperature and humidity according to standards